BRAND CONGRUITY WITH PARENT BRAND MEMPENGARUHI GREEN PURCHASE BEHAVIOR? - Simamora, Elisabeth Rotua; Graciafernandy, Maria Augustine (Solusi, 2023)
This research aims to analyze the factors that influence the perceived value of environmentally friendly products on purchasing behavior for environmentally friendly brand products. The aim of this research is to build a comprehensive model and test the relationship between attitudes towards parent brand and self-brand congruity. Attitude toward green brand extension is used to mediate the relationship between the two constructs, namely the green brand perceived value and green brand purchase behavior. Respondents in this research were users of environmentally friendly fashion, namely Levi's products, The Body Shop in Semarang. The sampling technique used was purposive sampling technique. The questionnaire distributed in this research was 444 respondents. Only 400 questionnaires could ultimately be used in this research. The data analysis technique in this research uses PLS-SEM with WarpPLS version 7.0. The research results show that: (1) attitudes towards the parent brand and self-brand congruity have a positive effect on the green brand perceived value (2) green brand perceived value has a positive effect on attitudes towards green brand extension and (3) attitudes towards green brand extension have a positive effect on green brand purchase behavior.